GAME KEBIJAKAN 8 DEWA - Julyanto Wijaya; Jeanny Pragantha; Helmy Thendean (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Game “Kebijakan 8 dewa” is an education game about 8 Gods for kids, especially  for kids who have parents that’s already a Xiao Yao Pai Taoism follower or Buddhists. The 8 Gods are Li Tie Guai, Zhong Li Quan, Zhang Guo Lao, Lu Dong Bin, Han Xiang Zi, Lan Cai He, Cao Guo Jiu, and He Xiang Gu. This games is dedicated for kids who wants to learn about 8 gods and morale education.